Junie B., first grader : turkeys we have loved and eaten (and other thankful stuff) - Park, Barbara (Junie B. Jones, 2012)
To celebrate the Thanksgiving holiday, Mr. Scary's first grade class prepares a Thankful List for the school contest, but Junie B. Jones finds it hard to be grateful for squash or Tattletale May.